2019
DOI: 10.1016/j.aller.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid affects immunological and inflammatory mediator levels and restores lung pathological features in asthmatic rats

Abstract: The results indicated a preventive effect for RA on immunological and inflammatory mediators as well as lung pathological changes in asthmatic rats which were comparable or even more potent than that of dexamethasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Previously, increased total WBC and neutrophil and eosinophil percentage in lung lavage of OVA-sensitized rats were shown [23,26]. Increased percentages of eosinophils were also demonstrated in sensitized animals and asthmatic patients that correlated with the severity of asthma and supported the results of the present study [27]. Activated eosinophils are critical in allergic reactions and induce respiratory hyperactivity in asthma [28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previously, increased total WBC and neutrophil and eosinophil percentage in lung lavage of OVA-sensitized rats were shown [23,26]. Increased percentages of eosinophils were also demonstrated in sensitized animals and asthmatic patients that correlated with the severity of asthma and supported the results of the present study [27]. Activated eosinophils are critical in allergic reactions and induce respiratory hyperactivity in asthma [28].…”
Section: Discussionsupporting
confidence: 90%
“…Activation of monocytes also contributes to asthma pathogenesis by releasing reactive nitrogen species, total free radicals, and proliferation of 2-like lymphocytes in patients with asthma [33]. Both animal and human studies have shown increased PLA 2 and TP in asthma [27,34]. Consequently, higher levels of PLA 2 and TP in the BALF of asthmatic rats also confirm the induction of an animal model of asthma in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In asthmatic rats, rosmarinic acid (0.125, 0.250, and 0.500 mg/ml) decreased the levels of IL-4, PLA2, IgE, and total protein, and increased the IFN-/IL-4 ratio in the BALF. Lung pathological changes induced by OVA were improved by rosmarinic acid treatment ( Shakeri et al, 2019 ). The findings of these works suggest a therapeutic effect for the extract of O. basilicum and its constituent, rosmarinic acid, on asthma ( Eftekhar et al, 2018a ; Eftekhar et al, 2018b ; Eftekhar et al, 2019a ).…”
Section: Resultsmentioning
confidence: 99%
“…However, future studies in vivo settings are required to unveil the underlying protective mechanism of RA. In another study, Shakeri et al ( 2019 ) investigated the effects of RA on OVA-induced asthma and its influence on lung pathology of OVA-sensitized asthmatic rats. RA treatment significantly abridged IL-4, IgE, phospholipase A 2, and total protein levels but increased the IFN-γ/IL-4 ratio.…”
Section: Pharmacological Properties Of Ramentioning
confidence: 99%